PERKEMBANGAN FDI KE INDONESIA DAN LANGKAH KEBIJAKAN YANG DIPERLUKAN - kemu, Suparman zen (Jurnal Kajian Ekonomi dan Keuangan, 2011)
Foreign Direct Investment (FDI] plays an important role in Indonesia economy, since it brings not only capital but also technology and marketing network. Indonesian economy also transforms from the poor country to low middle income country since early 1970's. From the observation, writer recognized that in 2010, the FDI to Indonesia grows quite significant. Three sectors' namely manufacture, mining, and transportation are the important sector that attracted more foreign investor. However, other minor sectors such as electricity, energy, and clean water still record low value since they are still dominated by state own enterprises. To this extence, government of Indonesia has to relax the monopoly of SOE to these sectors and give the opportunity to FDI to involve in these businesses. This year, Government is processing the regulation regarding tax holiday incentives that expected to boost further FDI to Indonesia.